Penyuluhan Hukum Mengenai Penanggulangan Penyakit Masyarakat di Kalangan Remaja di Kelurahan Pakuhaji Kecamatan Pakuhaji Kabupaten Tangerang - Dippo Alam; Sri Jaya Lesmana; Tina Asmarawati (Universitas Majalengka, 2023)
In September 2022, a team of lecturers from the Faculty of Law, Syekh Yusuf Islamic University, held an outreach with the agenda of preventing community diseases among adolescents in Pakuhaji sub-district, Pakuhaji district, Tangerang Regency. The material discussed was about preventing drug abuse, preventing trafficking in persons within the scope of the sub-district, and strengthening the participation of mass organizations in the community. This activity lasted only one day and was attended by all village officials and all elements of society, especially youth. At the end of the meeting, the lecturer team opened a discussion room where the participants asked many questions about the material. The activity was closed with a plan to establish further cooperation between Pakujahi Sub-district Government and the Faculty of Law of UNIS.